Positive education: Exploring students’ well-being framework in Indonesia - Yoga Setyo Wibowo; Farida Agus Setiawati; Siti Rahmi Qodriah; Yulia Ayriza (LPMPP Universitas Negeri Yogyakarta, 2021)
Positive education is a general term to describe an intervention and an empirically validated program that draws on positive psychology to promote students’ well-being. To date, there is no well-being measurement developed specifically for use in the Indonesian context. This article explores positive education, its relation to students’ well-being, and its relationship to the concept of the Positive Emotions, Engagement, Relationships, Meaning, and Accomplishment (PERMA model) in the Indonesian context. The sample used was 434 students in Yogyakarta Province. The data were analyzed using exploratory factor analysis and confirmatory factor analysis. The research instrument was adapted from the Positive Affect and Negative Affect Scale for Children (PANAS-C), the EPOCH (Engagement, Perseverance, Optimism, Connectedness, and Happiness), Measure of Adolescent Well-being, and Meaning in Life Questionnaire (MLQ). The results showed that (1) the well-being of students in Indonesia is structured into eight dimensions: pleasure, passion, excitement, engagement, relationship, presence, search, and accomplishment, and (2) confirmatory factor analysis shows that the eight dimensions show a better fit model than the PERMA model. Therefore, it is concluded that the well-being of high school students in Indonesia does not follow the